Analysis of Land Price Value In Tenayan Raya District as An Urban Service Center - Lintang Cahyaning Pratiwi (Journal Research of Social Science, Economics, and Management, 2025)
The phenomenon of rising land prices around the government office area in Pekanbaru City has become a significant concern due to its consistent increase since the development of these offices. This research aims to analyze the factors influencing these escalating land prices, providing insights into the underlying determinants. Employing the hedonic pricing method, the study examines how internal and external characteristics of land contribute to its value. The findings reveal that several factors significantly affect land prices, including proximity to the main road, distance to the city center, and accessibility to healthcare facilities. Additionally, community occupational characteristics, such as private employees, entrepreneurs, traders, and civil servants, also play a crucial role in shaping land prices. These results highlight the interplay between accessibility, occupational factors, and infrastructure development in determining land value. The study concludes that understanding these factors is essential for policymakers and urban planners to manage land use and development effectively, ensuring sustainable urban growth and equitable access to land resources.